2002
DOI: 10.1002/clc.4960250408
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aortic valve replacement on N‐terminal natriuretic propeptides in patients with aortic stenosis

Abstract: SummaryBackground: Increased plasma concentrations of natriuretic peptides have been demonstrated to be associated with increased intracardiac pressure and left ventricular (LV) hypertrophy. After aortic valve replacement (AVR) in aortic stenosis patients, there is a relief of the left outflow obstruction with a substantial hemodynamic improvement. This is followed by a gradual regression of the LV hypertrophy.Hypothesis: After AVR, reduction in LV filling pressure is expected to occur rapidly, while regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
2
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 20 publications
2
7
2
1
Order By: Relevance
“…Previously, ANP levels have been evaluated in AS patients and found to mirror symptom onset [15]. In addition, temporal changes in ANP values have been evaluated separately [6]. In our study, N-ANP levels were significantly higher in AS patients than in the controls, and they decreased significantly following surgery, in accordance with previous reports.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Previously, ANP levels have been evaluated in AS patients and found to mirror symptom onset [15]. In addition, temporal changes in ANP values have been evaluated separately [6]. In our study, N-ANP levels were significantly higher in AS patients than in the controls, and they decreased significantly following surgery, in accordance with previous reports.…”
Section: Discussionsupporting
confidence: 82%
“…Although it has previously been shown that the plasma NP level is related to disease severity in AS, with decreased levels following surgery [6], the association between arrhythmogenic complications following surgery for AS and NP has not been studied yet. Increased atrial NP (ANP) levels before and after surgery concomitant with temporal changes in echocardiographic findings might help to elucidate the pathophysiology of AF and the increased morbidity associated with AF after surgery.…”
Section: Introductionmentioning
confidence: 99%
“…The BNP level reflects the severity of heart failure, is associated with LV structure and function in severe AS as well as is an independent predictor of complication and outcome after AVR [10][11][12][13][14][15]. Moreover, it is strongly related to the development of symptom onset and increases progressively with worsening postoperative New York Heart Association (NYHA) functional class [11].…”
Section: Introductionmentioning
confidence: 99%
“…The circulating levels of these peptides are known to be elevated in response to increased cardiac wall stress and myocardial hypertrophy in states of pressure and/or volume overload [5,6,7,8]. Chronic aortic regurgitation (AR) or aortic stenosis (AS) is known to be associated with increased volume and/or pressure overload of the left ventricle (LV) leading to myocardial hypertrophy with LV dilatation and failure [9,10,11,12]. However, little data are currently available regarding the relationship between NT-proBNP levels and clinical characteristics, LV function or LV mass index (LVMI) in patients with chronic severe aortic valve diseases [13,14].…”
Section: Introductionmentioning
confidence: 99%